Impact of Heavy Metal Accumulation on Physiological and Immunological Parameters in Type 2 Diabetes Patients - Hussien, Nour Alaa Aldein (American Journal of Bioscience and Clinical Integrity, 2026)
Background & Aim: Heavy metal exposure has been associated with metabolic alteration and inflammation, which could promote the progression of type 2 diabetes mellitus (T2DM). Heavy metals along with detection limit results on physiological and immunological parameters were carried out in T2DM patients. Materials & Methods: Case-control study was performed among 110 T2DM patients and 110 healthy subjects at Kirkuk Teaching Hospital (May–September 2025). Fasting Blood Glucose (FBS), HbA1c, liver function enzymes (ALT, AST, ALP), pro-inflammatory cytokines (TNF‑α, IL‑6 and IL‑1β) and blood levels of Pb, Ni and Cd were evaluated. Relationships of heavy metals to clinical and immunological parameters were examined. Results: FBS (168.4 ± 35.2 vs 92.6 ± 11.8 mg/dL) and HbA1c (8.3 ± 1.2 vs 5.4±0.5%) were significantly higher in T2DM patients compared to the controls (p <0.001). Liver enzymes, TNF‑α, IL‑6 and IL‑1β and blood heavy metals (Pb: 12.3 ± 3.1 µg/dL, Ni: 7.8 ± 2.4 µg/L,Cd: 1.9 ± 0.7 µg/dL) levels were significantly higher among patients compared with controls (all p < 0.01). Pb and Cd were strongly correlated with FBS, HbA1c and cytokines levels (r = 0.39–0.61, p < 0.01), whereas Ni exerted a less pronounced but significant correlation. Conclusion: Chronic heavy metals exposure is related with unsatisfactory glycemic control and systemic inflammation in T2DM patients, which underscores the significance of environmental toxicants as a modifiable risk factor.